Dealing with Alternatively Organized Workers: Recruitment and Retention Strategies among Danish Shop Stewards - Ilsøe, Anna (Nordic Journal of Working Life Studies, 2013)
Membership rates of alternative unions that offer individual juridical guidance and assistance but rarely contribute to collective bargaining are increasing in Denmark. Conversely, the overall membership rates of traditional unions that negotiate collective agreements are decreasing. This means that local shop stewards often face a mixed environment of workers in traditional unions and workers in alternative unions at the individual workplace. Surveys have indicated that shop stewards split into two groups when dealing with non-members at the workplace. Half of them choose to represent non-members (pull strategy), whereas the other half choose not to (push strategy). This article presents an explorative case study of the recruitment and retention strategies used by two shop stewards in two different companies with significant groups of alternatively organized workers. A case with sector-level wage setting and a case with local-level wage setting within the manufacturing sector are compared. Results suggest that shop stewards in both types of settings tend to combine push and pull strategies, because they serve different purposes. Push strategies help retain existing members of the traditional unions, whereas pull strategies are necessary to recruit new members. Local-level wage setting seems to offer more opportunities for shop stewards to make use of push and pull strategies than sector-level wage setting. Local negotiators can be efficient organizers, because they are able to demonstrate visible advantages of union membership on a regular and individual basis. However, it is also a high-risk project that among others depends on the support from the local union office.